A 42‐Year Observation of Traditional Periodontal Therapy Supplemented by Dental Implants. Issue 2 (1st May 2013) - Nevins, Myron; Dornbush, Jeffrey; Koo, Samuel; Depaoli, Massimo; Kim, David M.
Abstract : Introduction: Periodontal disease can be successfully treated and maintained for an extensive period. A small category of patients demonstrates aggressive periodontitis (previously known as refractory periodontitis), which does not respond appropriately to the traditional therapy even when the patient's compliance is excellent. Case Presentation: This case report presents a long‐term observation of dental implants replacing teeth with a compromised maxillary periodontium. Implants were placed initially in 1989 and 1993 to supplement some remaining teeth. These implants continue to function after 23 years. The maxillary central incisors were fractured in 2005 and replaced with two platform‐switched implants. This area has demonstrated crestal stability after 7 years. Conclusion: A long‐term observation of this patient demonstrated that dental implants are successful in periodontally compromised patients, and the crestal bone remained stable around the platform‐switched implants.